INTEGRASI PENDIDIKAN KARAKTER DAN NILAI AGAMA DALAM KURIKULUM PAUD: STUDI LITERATUR - Dinan Anggun Setyowati; Ahmad Suriansyah; Novitawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the integration of character education and religious values into the Early Childhood Education (ECE) curriculum through a literature review approach. Character education integrated with religious values is considered a fundamental component in shaping children’s personality, morality, and spirituality from an early age. Values such as honesty, responsibility, empathy, and patience are not only conveyed through cognitive aspects but are also internalized through contextual activities such as storytelling, role-playing, communal worship, and everyday modeling. The findings indicate that the success of this integration is highly influenced by the role of educators, the synergy between schools and families, and a curriculum designed to be adaptive. Furthermore, challenges such as limited teacher competencies, the lack of appropriate learning media, and time constraints are obstacles that must be addressed through ongoing professional development and the support of all stakeholders. This study concludes that the integration of religious values into character education at the early childhood level is an effective strategy for fostering a generation that is not only intellectually capable but also morally and spiritually strong. Through a holistic and collaborative approach, these noble values can be consistently instilled from an early age, serving as a crucial foundation for children's future lives.